HIV Situation in the Penitentiary System of the Russian Federation - S. B. Ponomarev; S. A. Sterlikov; А. Yu. Mikhaylov (Туберкулез и болезни лёгких)
The objective: to identify promising directions for prevention of HIV incidence mortality on the basis of analysis of changes in HIV situation assessing the effectiveness of interventions in penitentiary units.HIV infection has traditionally been a critical issue for the penitentiary system worldwide and in Russia particularly. Recently, Russia has managed to achieve positive changes in the epidemic situation: by 2020, HIV incidence reduced to 852.8 per 100,000 (including 2,433.6 in remand prisons and 122.8 in correctional institutions); HIV prevalence was 10,512.8 per 100,000; HIV mortality was 98.3 per 100,000; HIV lethality was 0.9 per 100,000 people living with HIV.The proportion of HIV infection as a cause of death decreased from 32.0 in 2016 to 20.5 in 2020. The positive changes developed faster compared to civilian health care and occurred during the growing coverage with antiretroviral therapy which increased from 21.7% in 2014 to 89.6% in 2020. The following problems persist: high prevalence of HIV infection among female inmates (19,275.0 versus 9,769.2 among male inmates per 100,000), the high proportion of HIV/hepatitis C co-infection (49.0%; 95% CI 48.6-49.5), and the low coverage with hepatitis C treatment (0.5% of the total number of persons with co-infection). Promising directions for the prevention of HIV incidence and mortality are related to stable supply of antiretroviral drugs, improved patient adherence to treatment, and expanding treatment for HIV/hepatitis C co-infection.